The Use of Soft Power in Russian Propaganda: An Analytical Study - Ibrahim, Ali Mahmoud (ALBAHITH ALALAMI, 2025)
Objectives: The research aims to uncover the rhetorical mechanisms employed by Russian President Vladimir Putin in utilizing soft power tools within his propaganda discourse. It seeks to identify the key soft power instruments emphasized in Russian rhetoric during the Ukraine crisis and analyze the propaganda techniques based on soft power utilization within the context of official Russian political discourse.Methodology: This research falls under qualitative analytical studies, where the researcher employed Critical Discourse Analysis (CDA), based on Norman Fairclough's three-stage model: text analysis, discourse analysis, and social context analysis. A purposive sample of two official speeches by President Putin was selected: the first is an article published on July 12, 2021, titled "The Historical Unity Between Russians and Ukrainians," and the second is a televised speech delivered on February 24, 2022, coinciding with the start of the Russia-Ukraine war.Results: The Russian discourse utilized soft power through psychological and emotional influence, linking the present to nationalist historical narratives. Putin relied on symbolic slogans such as "Russian Unity" and "Multinational Russia" to reinforce his political stance, justifying the war on Ukraine as a "legitimate" action to protect Russia's historical unity and culture. The independence of Ukraine was depicted as the result of a foreign conspiracy. The discourse demonstrated the integration of various soft power tools: historical symbolism, cultural influence, diplomacy, economic elements (e.g., gas resources), and military doctrine. Linguistic techniques included threats, intimidation, historical metaphors, religious symbols, euphemism, repetition, and rhetorical questions. Putin successfully rebranded Russia as a "great power," delegitimized the West and Ukraine, and positioned Russia as the protector of shared values and history.Conclusion: Russian propaganda reflects an advanced use of soft power, integrating symbolic dimensions with modern communication strategies to reshape domestic and international public opinion. The research shows that Putin employed narrative and historical mechanisms to persuade the Russian public and justify Russia's stance internationally, highlighting the effectiveness of soft power as a propaganda tool in contemporary international relations.